Cytotoxic, Antiproliferation, and Necrosis Effects of the n-Hexane Fraction Extract of Gendola Leaf (Basella rubra Linn.) - Sri Hartini Harianja; Salni Salni; Subandrate Subandrate (Jurnal Kimia Sains dan Aplikasi, 2020)
Breast cancer is the second most common cancer in women. Several studies have been conducted on natural materials to see the ability of its activity as a new anticancer compound. The purpose of this study was to determine the cytotoxic activity of Gendola leaf (Basella rubra Linn.) extracts and fractions, in inhibiting proliferation and inducing apoptosis of T47D breast cancer cells. The design of this study was experimental laboratory research using the in-vitro method. Cytotoxic and anti-proliferation tests on T47D cancer were using the MTT method, and the apoptosis test was using the flow cytometry method. Cytotoxic of extracts and fractions of n-hexane Gendola leaves were tested with a concentration series of 1000; 500; 250; 125; 62.5 μg/mL and doxorubicin was studied a series concentration of 0.5; 0.25; 0.125; 0.0625; 0.03125 μg/mL for 24 hours. Antiproliferation test used n-hexane fraction with a concentration series of 1IC50, ½IC50, ¼IC50, and ⅛IC50 with an incubation time of 24 and 48 hours. Apoptosis test utilized n-hexane fraction with a concentration series of 1IC50, ½IC50 with an incubation time of 24 hours. The results showed that the ethanol extract had IC50 424 μg/mL, n-hexane fraction 292 μg/mL. The n-hexane fraction had an anti-proliferation effect at a concentration of 1IC50 within 32 hours but was unable to induce T47D cell apoptosis. These results indicate that the n-hexane fraction of Gendola leaf has a cytotoxic effect, which can inhibit proliferation, that is unable to induce apoptosis but induce necrosis of T47D breast cancer cells.